2007
DOI: 10.1177/000348940711600411
|View full text |Cite
|
Sign up to set email alerts
|

Alström Syndrome: Progressive Deafness and Blindness

Abstract: Alström syndrome is a very rare, genetically transmitted disorder that affects special sense functions, resulting in progressive visual and auditory impairment. The diagnostic criteria for this disorder are presented, and the differential issues between it and other, similar syndromal forms of sensory and multisystem dysfunction are discussed. A report of 2 siblings so involved is summarized. The disability of other organs is considered, namely, the kidney, the heart, and the metabolic and endocrine systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…Consistently, patients with multisystem ciliopathies such as Alström, Bardet-Biedl and Joubert syndromes often suffer from impairment of retinal, olfactory and auditory function. Progressive SNHL is a well-known feature of AS [Welsh et al, 2007]. However, age of onset and severity of hearing loss is variable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, patients with multisystem ciliopathies such as Alström, Bardet-Biedl and Joubert syndromes often suffer from impairment of retinal, olfactory and auditory function. Progressive SNHL is a well-known feature of AS [Welsh et al, 2007]. However, age of onset and severity of hearing loss is variable.…”
Section: Discussionmentioning
confidence: 99%
“…While progressive decline in pure tone sensitivity has been documented in patients with AS [Bahmad Jr. et al, 2014; Welsh et al, 2007], the auditory profile has not been fully characterized. Distortion product otoacoustic emissions (DPOAEs) and auditory brainstem responses (ABRs), which are critical assessments for discerning sensory versus neural hearing loss, have been reported for two siblings [Bahmad Jr. et al, 2014], but have not been reported for a cohort study.…”
Section: Introductionmentioning
confidence: 99%
“…However, age of onset and severity is variable and can develop anytime from onset in infancy to adulthood [21,22]. Further, chronic and acute otitis media in childhood often exacerbates the sensorineural deficits with a component of conductive hearing loss [4].…”
Section: Alström Syndrome Clinical Overviewmentioning
confidence: 99%
“…Greater than 85% of patients present with bilateral sensorineural hearing loss, usually beginning in the first decade of life. The hearing loss is often compounded by chronic otitis media and glue ear [Alström et al, 1959, Marshall et al 2005, Marshall et al 2007,Welsh 2007, Marshall et al 2011]. Other clinical features include truncal obesity, type 2 diabetes mellitus in 95% of children over the age of 15 years, hypertriglyceridemia, hypercholesterolemia, dilated or restrictive cardiomyopathy, hypogonadism, glomerulosclerosis leading to progressive renal failure, steatosis, steatohepatitis, or cirrhosis of the liver [Marshall et al, 2011].…”
Section: Introductionmentioning
confidence: 99%